2010
DOI: 10.1007/s00464-010-1014-1
|View full text |Cite
|
Sign up to set email alerts
|

Subtotal gastrectomy with D2 dissection by minimally invasive surgery for distal adenocarcinoma of the stomach: results and 5-year survival

Abstract: D2 subtotal gastrectomy performed by MIS is reproducible and safe. The long-term outcomes and 5-year survival are acceptable. Extended lymphadenectomy was carried out for both EGC and AGC so as to ensure adequate nodal clearance and compensate preoperative underestimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
157
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(171 citation statements)
references
References 37 publications
7
157
1
6
Order By: Relevance
“…Patients with a BMI of more than 30 were excluded from this study; as a result, the median BMI was 21.8. In western countries, the median BMI was reported as 26-29, and higher morbidities (10%-26% as grade 1-4 adverse events) than that in this study (9.1%) were demonstrated [22,23]. Thus, BMI should be taken into consideration to interpret the morbidity results.…”
Section: Discussionmentioning
confidence: 89%
“…Patients with a BMI of more than 30 were excluded from this study; as a result, the median BMI was 21.8. In western countries, the median BMI was reported as 26-29, and higher morbidities (10%-26% as grade 1-4 adverse events) than that in this study (9.1%) were demonstrated [22,23]. Thus, BMI should be taken into consideration to interpret the morbidity results.…”
Section: Discussionmentioning
confidence: 89%
“…Six of the included studies were published in English, and one published in Chinese . Four studies were from Korea Kang et al, 2012;Yoon et al, 2012;Hyun et al, 2013) and one from Turkey (Pugliese et al, 2010), and two from China Huang et al, 2012). The baseline characteristics and quality assessment of all included studies were listed in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…By carefully screening titles, abstracts and even full texts, seven retrospective studies (Pugliese et al, 2010;Huang et al, 2012;Kim et al, 2012;Yoon et al, 2012;Kang et al, 2012;Zhang et al, 2012;Hyun et al, 2013) met all inclusion criteria entered in this meta-analysis. In all, our meta-analysis included 2235 patients with gastric cancer, in which 1473 patients had undergone LG, and 762 had undergone RG.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Overall, several reports documented that operative time was significantly longer for the robotic procedure ranging from 202 to 439 minutes compared with 171 to 361 minutes in laparoscopy6, 7, 16 (Table 1). Increase in operative time was initially attributed to the docking time, but this no longer seems to be a contributing factor 15.…”
Section: Perioperative Outcomesmentioning
confidence: 99%
“…Many reports comparing robotic and laparoscopic gastrectomy revealed that there is significant reduction in blood loss with a range of 46–176mL with robotic approach and 34–212mL with laparoscopic approach6, 7, 16 (Table 1). Meanwhile, data from a recent multicenter non‐randomized comparative trial showed that there was no difference in estimated blood loss between robotic and laparoscopic gastrectomy 29.…”
Section: Perioperative Outcomesmentioning
confidence: 99%